Riba, profit rate, Islamic rate, and market equilibrium - Yusoff, Mohammed (International Islamic University Malaysia, 2013)
Muslim economists have suggested the profit rate to replace ribÉ in an Islamic economic system. While this suggestion is a step in the right direction, it still has problem since not all profits are ÍalÉl, as for example, profits from gaming and liquor businesses are definitely ÍarÉm. This paper discusses the concept of ribÉ and differentiates it from the profit rate and Islamic rate. As ribÉ is prohibited in Islam, this paper explains the concept of Islamic rate, which is lawful in Islam as it is directly derived from the profits of ÍalÉl business activities. The Islamic rate is the clearing mechanism in the money market and good market. The paper has also derived the money market equilibrium and good market equilibrium conditions or the IS-LM framework which can be used to analyze the efficacy of monetary and fiscal policy in an Islamic state. In order to clear the notion that the conventional banking system has been dictating the decision makings in the Islamic banking system in Malaysia, the paper uses the Toda-Yamamoto technique of Granger causality test to see the causality between the Islamic investment deposit rates, which are Islamic rates, of Islamic banking and the fixed deposit rates, which are ribÉ, of the conventional banking. The results are not conclusive as a number of Islamic investment deposit rates have caused the fixed deposit rates while some fixed deposit rates cause Islamic investment deposit rates, and yet some others show that there are no causality between the two types of rate.